The Effect of Affiliator Digital Promotion Strategies on Increasing Consumer Shopping Interest - Widiyan, Widiyan; Nazwha Dwi Alfiani; Achmad Mubarok; Mukarto Siswoyo (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to analyze the influence of digital affiliate promotion strategies on consumer interest in shopping, particularly among students studying at the Faculty of Social and Political Sciences, Swadaya Gunung Jati University, Cirebon. Using a quantitative data-based approach, data was collected using questionnaires distributed to 118 research participants. The findings of this study reveal that the digital marketing strategies implemented by affiliates significantly contribute to increasing consumer interest in shopping, with a significance level of 0.000, which is below the threshold of 0.05. Product, price, location, and promotion factors were found to have a positive impact on consumers' purchasing decisions. Simple linear regression analysis shows that approximately 72.9% of the variation in consumer shopping interest can be explained by the affiliate's digital promotion strategies. This study concludes that companies and affiliates need to consider these elements when designing digital marketing strategies to enhance product appeal and maximize sales potential.